The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0104-66322010000400006
|View full text |Cite
|
Sign up to set email alerts
|

Ozone application in water sources: effects of operational parameters and water quality variables on ozone residual profiles and decay rates

Abstract: -Systematic ozonation tests were conducted by means of a mobile pilot plant. Water source 1 was a low turbidity stream with very low solids content and very low turbidity, apparent color and alkalinity. Water source 2 was reservoir water with higher turbidity, solids content and alkalinity than source 1. The ozone plant was a counter-current contactor composed of four columns in series. Variations in contact time, in the feed gas concentration (in terms of percent by weight of ozone) and in splitting of the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…A Spectroquant ® Ozone Test kit 100607 (Merck, Darmstadt, Germany) was used to confirm the concentrations determined by the standardized method. Considering the previous data on the stability of O 3 in ultrapure water, which was previously considered the best type of water for increased O 3 stability [26,32], changes were applied in its physicochemical parameters. Samples of ultrapure water with these different physicochemical characteristics are displayed in Table S1, and the changes are related to the temperature and pH.…”
Section: Standardization and Quantification Of O 3 In Water Using The Spectrophotometric Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A Spectroquant ® Ozone Test kit 100607 (Merck, Darmstadt, Germany) was used to confirm the concentrations determined by the standardized method. Considering the previous data on the stability of O 3 in ultrapure water, which was previously considered the best type of water for increased O 3 stability [26,32], changes were applied in its physicochemical parameters. Samples of ultrapure water with these different physicochemical characteristics are displayed in Table S1, and the changes are related to the temperature and pH.…”
Section: Standardization and Quantification Of O 3 In Water Using The Spectrophotometric Methodsmentioning
confidence: 99%
“…The air is bubbled directly into the water through an air outlet. After this ozonation process, it is necessary to perform the quantification and determination of the dissolved O 3 concentration [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Summerfelt & Hochheimer ; Summerfelt et al . ; Lage Filho ). Briefly, the highly reactive nature of ozone means that it decomposes to free radicals and other ozone‐derived chemical species, leaving ‘residual’ dissolved ozone.…”
Section: Factors That Influence Direct Ozonation In Aquaculturementioning
confidence: 97%
“…The rate of ozone decay increases with time after deployment, whilst higher flow rates (differing hydraulic retention time) or low initial dosages and high water pH may reduce ozone concentration (previously reviewed by Lage Filho ; Gonçalves & Gagnon ; Rahmadi & Kim ). Sharrer and Summerfelt () also suggested that bacteria embedded within particulate matter, or that formed bacterial aggregates, provided shielding from oxidation.…”
Section: Factors That Influence Direct Ozonation In Aquaculturementioning
confidence: 99%